A 5 year clinical experience of Laparoscopic Appendicectomy - Shrestha, S K; Dangol, U MS; Sharma, S K (Journal of Nepal Health Research Council, 2011)
Â <!–> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> Background: Although laparoscopic appendicectomy is now a common practice, it has not become the gold standard like in cholecystectomy. Aim of our study is to compare with operation time and hospital stay found in available literatures. Methods: All laparoscopic appendicectomies performed between January 2004 and February 2009 were retrospectively reviewed for age, sex and operation time length and hospital stay. Appendicitis with signs of perforation was treated by open midline laparatomy and the ones with lump formation were treated conservatively. Results: A total of 48 patients underwent laparoscopic appendicectomies during this period (female 26 and male 22) and mean age was 27.2 years (6-77). The mean operating time was 56.6 minutes (40-120 minutes). The mean hospital stay was 4.7 days (3-8 days). Conclusions: Laparoscopic appendicectomy is a feasible and safe in simple appendicitis. Although the number of cases of laparoscopic appendicectomies is a small for five year period, the mean operation time and mean hospital stay is comparable to the literatures. Â Key words: appendicectomy, laparoscopy, operation time, hospital stay